Trend analysis of complex release and re-grasp skills on the high bar - Samuels, M.; Irwin, G.; Kerwin, D.; Gittoes, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to examine the influence of the Code of Points on the frequency and type of Kovacs performed on the high bar by elite gymnasts. Video recordings of high bar performances were collected from the 2000 Sydney Olympic Games and 2006 Aarhus World Championships. Development of the Kovacs skill within the Code of Points was informed by a trend analysis of the type and frequency of release skills at the two international competitions. Kovacs variations contributed to 50% of the release skills at the Olympic Games and 40% post qualification round at the World Championships. The high frequency of the Kovacs was attributed to the increase in associated difficulty ranking, potential to increase difficulty through shape and twisting option and durability within the Code of Points. Biomechanical analysis is required for further understanding of the completion and development of the Kovacs.